Meraih Mutu Sekolah Melalui Data Mutu: Suatu Tinjauan - Nurmaini MY (Universitas Batanghari Jambi, 2019)
Increasing quality education is responsibility of all stake holders, but the one that most probably demanded to have big responsibity is the principal of the school. Principal must know what to do to improve their school better. Internal and external quality assurance contain quality data. Internal and external quality data is significant to grow the school beter. The problem is most principal don’t use these data in improving their schools. To meet client satisfaction, school must develop school continuously. Internal data in internal quality assurance System ( SPMI ) can be used to develop school as well as external data of quality assurance ( SPME / accreditation) to meet SNP because Internal quality assurance ( SPMI ) aims to help school develop their program and avoid the gaps between ideal condition and fact based on school self evaluation. Cycling procedure owned by SPMI make the development of school suit to its needs (Stating the standard as National Standard, mapping school condition for finding weakness and stenghthness, plan and conduct the plan, montoring and audit). Following this cycles make schools reach proper improvement. Other quality data is external data which can also be used by principal to improve its school because this data contains recommendation to meet SNP after assessed by assessor. Thus all principal make use both of internal and external quality data to achieve school quality.